DEFLATION RISKS OF SOIL COVER IN VOLYN REGION - Pysarenko, P. V.; Matviichuk, B. V.; Matviichuk, N. H. (Scientific Progress & Innovations, 2020)
Boggy and peat-boggy soils on different rocks and alluvial deposits, lowland peat and peat-boggy soils and sod carbonate soils mainly on the eluvium of dense carbonate rocks are characterized by the greatest heterogeneity in terms of sensitivity to wind erosion. Medium-deep sandy-loam black soils, semi-loam podzo-lized black soil and deep medium-loam black soils are the most homogeneous according to this indicator. The least sensitive to wind erosion are boggy and peat-boggy soils on different rocks, lowland peat and peat-boggy soils and sod carbonate soils mainly on the eluvium of dense carbonate rocks. The soils in the north of the region, which have a very high content of organic matter, are the least sensitive to wind erosion The southern part of the region, where soils have a heavier mechanical composition, is characterized by a mod-erate sensitivity level to wind erosion. The smallest share of the fraction sensitive to wind erosion was found in the soils of Horokhiv (0.42), Liubeshiv (0.42) and Ivanychiv (0.43) districts. The most homogeneous con-ditions in terms of soil sensitivity to erosion according to variation coefficient of soil fraction content, which may be affected by wind erosion are in Lutsk (CV=5.12 %), Horokhiv (CV=6.24 %) and Kivertsi (6.8 %) districts. The most heterogeneous conditions according to this criterion are in Liubeshiv (CV=18.18 %), Ratniv (CV=13.47 %) and Shatsk (11.45 %) districts. The highest level of wind erosion is forecasted for the administrative districts of the region, which are located in the west and northwest of the region. The fore-casted area with practically no or little deflation is most characteristic of the south-eastern districts. The ratio between areas with small and moderate levels of wind erosion determines the average level of soil ero-sion losses in the administrative district.